fMRI of Working Memory Impairment after Recovery from Subarachnoid Hemorrhage - Ellmore, Timothy M.; Rohlffs, Fiona; Khursheed, Faraz (Frontiers in Neurology, 2013)
Recovery from aneurysmal subarachnoid hemorrhage (SAH) is often incomplete and accompanied by subtle but persistent cognitive deficits. Previous neuropsychological reports indicate these deficits include most prominently memory impairment, with working memory particularly affected. The neural basis of these memory deficits remains unknown and unexplored by functional magnetic resonance imaging (fMRI). In the present study, patients who experienced (SAH) underwent fMRI during the performance of a verbal working memory paradigm. Behavioral results indicated a subtle but statistically significant impairment relative to healthy subjects in working memory performance accuracy, which was accompanied by relatively increased blood oxygen level dependent signal in widespread left and right hemisphere cortical areas during periods of encoding, maintenance, and retrieval. Activity increases remained after factoring out inter-individual differences in age and task performance, and included most notably left hemisphere regions associated with the phonological loop processing, bilateral sensorimotor regions, and right hemisphere dorsolateral prefrontal cortex. We conclude that deficits in verbal working memory following recovery from (SAH) are accompanied by widespread differences in hemodynamic correlates of neural activity. These differences are discussed with respect to the immediate and delayed focal and global brain damage that can occur following (SAH), and the possibility that this damage induces subcortical disconnection and subsequent decreased efficiency in neural processing.